ԶԼՄ–ների՝ որպես հասարակական– քաղաքական ինստիտուտի ձևավորման փուլերը և առանձնահատկությունները - Լիլիթ Խառատյան (ՀՀ ԳԱԱ հրատ.)
Правовое регулирование деятельности СМИ и журналистов в разные периоды становления и развития государств осуществлялось по–разному. В статье раскрывается сущность и динамика развития печатных и электронных СМИ, а также роль телевидения в системе СМИ в период становления информационного общества и новейших технологий. Особое внимание уделяется проблеме воздействия СМИ на формирование сознания личности,взаимоотношения СМИ, власти и демократического общества. Legal Regulations of the Media activities and journalists in different periods of formation and development of the states was carried out in different ways. The article reveals the essence and dynamics of the evolution of print and electronic media, as well as the role of television in the media system in the period of formation of the information society and new technologies. Particular attention is paid to the impact of the Media on the formation of of personal consciousness, the media relations, government and democratic society.
Keywords: Social Sciences; Sociology; Language and Literature